Sumptuous clothing and ornamentation in the Apocalypse - Neufeld, Dietmar (HTS teologiese studies, 2002)
Using different categories of social psychology on body decoration and dress, this article examines the author’s course of shifting political, moral, religious and eschatological values as reflected in the clothing and ornamentation motifs deployed in the narrative of the Apocalypse. The article focuses on questions such as the eschatological values betrayed by the author’s deployment of clothing and ornamentation themes, the meaning adduced from the passages in the Apocalypse where body surface is taken seriously, ancients’ connection of clothing and body decoration with the person and society, and the social values reflected by dress and ornamentation, such as honour/shame, status, boundaries, and identity personally and collectively.